2022
DOI: 10.3390/ijms23105655
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Extracellular Vesicles as Novel Biomarker Sources in Peritoneal Dialysis in Children

Abstract: Peritoneal dialysis (PD) represents the dialysis modality of choice for pediatric patients with end-stage kidney disease. Indeed, compared with hemodialysis (HD), it offers many advantages, including more flexibility, reduction of the risk of hospital-acquired infections, preservation of residual kidney function, and a better quality of life. However, despite these positive aspects, PD may be associated with several long-term complications that may impair both patient’s general health and PD adequacy. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…Recently, it was shown that exudate associated with wounds is a rich source of molecules and has recently been used to study the local tissue damage induced by snake venoms [14][15][16][17][18]49]. Moreover, several studies have shown that peritoneal exudate-derived EVs contain many EV biomarkers related to the local response to inflammation and disease progression [50][51][52][53]. However, isolating EVs from a biofluid is challenging with regard to yield, reproducibility, and purity [54].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that exudate associated with wounds is a rich source of molecules and has recently been used to study the local tissue damage induced by snake venoms [14][15][16][17][18]49]. Moreover, several studies have shown that peritoneal exudate-derived EVs contain many EV biomarkers related to the local response to inflammation and disease progression [50][51][52][53]. However, isolating EVs from a biofluid is challenging with regard to yield, reproducibility, and purity [54].…”
Section: Discussionmentioning
confidence: 99%
“…However, mesothelial cells have the ability to change their phenotype comparable to changes seen in epithelial-to-mesenchymal transition (EMT), which has been termed mesothelial-to-mesenchymal transition (MMT) ( 95 ). This has implications both in normal repair and pathological processes ( 94 , 96 , 97 ). PMCs participate in initiating and resolving serosal inflammation and repair by secreting various pro-, anti- and immunomodulatory mediators into the serosal fluid and submesothelial compartment.…”
Section: Discussionmentioning
confidence: 99%
“…In paediatric oncology, proteogenomic studies are furthering our understanding of relapse and treatment resistance in children with acute myeloid leukaemia, providing new approaches to predict relapse during disease progression, novel biomarkers and new targets for novel drug therapies (Stratmann et al, 2022 ). Other areas where proteomics provides value to prediction, diagnostics and personalised interventions include chronic kidney disease and peritoneal dialysis in children (Cummins et al, 2022 ; Trincianti et al, 2022 ), drug metabolism and personalised dose optimisation in children (Streekstra et al, 2021 ; van Groen et al, 2022 ) and the use of multi-omics derived biomarkers to develop prediction models in children with asthma to guide therapy (Golebski et al, 2020 ; Kang et al, 2022 ). Proteomics either in isolation or part of a multi-omics approach has revolutionised our ability to develop individual disease profiling across multiple areas of paediatrics with new diagnostic, predictive and prognostic methodologies, and new targets for novel drug development.…”
Section: Developing Biomarkers and Targeted Therapies To Treat Childh...mentioning
confidence: 99%